On-Farm Verification of Peanut Varieties in Rainfed and Lahar Laden Areas of Pampanga, Philippines - Mary Grace Gatan; Virgilio Gonzales (Philippine Association of Institutions for Research, Inc., 2014)
Lahar sediment areas represent drought-prone growing ecosystems due to their sandy texture and low organic matter. Peanut, a rainfed crop has been a common option in such areas, where yields are usually less than 1.0 t ha . Hence, on-farm trials were conducted in farmers' field to introduce and evaluate the drought-resistant varieties in relation to yield performance, reaction to diseases, profitability, farmers' acceptability and market preference. Introduced varieties were the pink-seeded NSIC Pn11 and red-seeded ICGV 99046 which were compared with red-seeded farmers' variety in wet and dry seasons. Varieties were arranged in randomized complete block design of four replicate farms. Pod yield of introduced varieties ranged from 2.4 to 3.0 tons/ha, higher than the yield obtained in farmers' variety (1.7-1.9 tons/ha) in both seasons. ICGV 99046 recorded the highest yield across two cropping seasons (2.9-3.0 tons/ha). High yield of introduced varieties was associated with greater pod number per plant, higher 100-seed weight, higher shelling percentage, longer number of days to maturity, and resistance to fungal diseases. Net farm income from adopting introduced peanut varieties was 123-230% higher than that obtained using farmers' variety. The growing of conventional farmers' variety resulted to low benefit cost ratio of less than 1.0 while the use of introduced varieties generated a benefit cost ratio of more than 1.0. Red-seeded varieties are predominantly preferred by farmers and market entities. The study demonstrated the advantage of adopting red-seeded ICGV 99046 for improving peanut yield, increasing farm income, and acceptability by farmers and market entities.